(untitled) (Indian Journal of Animal Production and Management, 2024)
An investigation was carried out to study the breeding and health care practices followed by the dairy farmers in five districts of Telangana state. From each district one mandal and from each mandal five villages were selected. The data was collected from 150 farmers through personal interview utilizing a schedule developed for the purpose.It was observed that majority of the farmers (91.33%) were aware of heat symptoms and importance of inseminating at the right time and AI was the choice of breeding for 83.33% of farmers. Majority of the farmers (70%) were getting their animal diagnosed for pregnancy of which 66% of them were adopting the pregnancy diagnosis only after 3 months. Lack of awareness about the disposal of placenta after its expulsion was 64.67% and throwing placenta on the streets in their vicinities. Only 38% of the farmers utilized services of a veterinarian, while 34% and 19.33% utilized services of para-veterinarians and from both, respectively. 96.67% were not taking general sanitary measures for sick and diseased animals and 55.33% farmers did not take any measures for ecto-parasite control.